Problemsof Local Floods and Their Relation to Bogor City Drainage Infrastructure System - Andi Setyo Pambudi (Universitas Djuanda, 2022)
Highland areas are not necessarily without flood problems, especially local flooding. The problem of poor drainage can be the cause of a local flood, as happened in Bogor City, West Java. Development evaluation related to local flooding in a city is an exciting topic to study further. The purpose of this evaluation is to answer the need for public information about the philosophy of flooding in the highlands, existing policies, and factors causing local flooding in Bogor City. The benefits of this analysis can also provide policymakers with input on strategic steps in the planning of urban drainage infrastructure systems, both in terms of physical channels, social approaches, and aspects of land carrying capacity within the ecological framework. The method used in this evaluation is in the form of literature studies and direct field observations of Bogor City's drainage infrastructure at specific points. The recommendation for the Bogor City government is to carry out comprehensive data collection and re-topography, namely by collecting data on buildings and drainage, determining the slope and height of the channel, and implementing risk management at each stage of its implementation. In addition, strict supervision and community participation in overseeing the development process and reducing waste disposal in the river supports the improvement of drainage development.